ADOPTION OF SHARIA FINTECH AND THE PAYLATER ECOSYSTEM: A COMPREHENSIVE ANALYSIS OF GENERATION Z'S IMPULSIVE BUYING BEHAVIOR WITHIN THE SPECTRUM OF MAQASHID SHARIA AND FINANCIAL RESILIENCE - Rohman Pranoto; Isrun Abdurahman; Rizaldy Alpiansyah; Miftah Wangsadanureja; Tatang Hidayat (Dirham : Journal of Islamic Economics, 2026)
The penetration of Buy Now Pay Later (BNPL) or paylater services has disrupted public consumption patterns, particularly among Generation Z in Indonesia. This study aims to analyze the impulsive buying behavior among Generation Z resulting from the use of paylater features through the perspective of Maqashid Sharia, specifically on the pillar of Hifdzul Mal (protection of wealth). This research employs a mixed methods approach combining quantitative and qualitative analyses, supported by a Systematic Literature Review (SLR) of literature and statistical data from the 2023-2025 period. The results indicate that transaction convenience and digital promotion manipulation trigger a significant surge in impulsive buying, resulting in an increased default ratio among the youth demographic. From the perspective of muamalah jurisprudence, although there are sharia-compliant paylater platforms utilizing Murabahah and Wakalah bil Ujrah contracts, their implementation often falls into the illusion of formal compliance without addressing substantive ethics. Generation Z's hyper-consumption behavior, which prioritizes tertiary needs (Tahsiniyat) through debt, contradicts the values of Hifdzul Mal and is classified as israf (extravagance) and tabdzir (wastefulness). Islamic financial literacy was found to be a crucial mediating variable in protecting Generation Z from the digital debt trap. This study recommends strengthening macro-prudential regulations, revitalizing the supervision of sharia boards, and providing comprehensive financial literacy education.